2016
DOI: 10.4014/jmb.1512.12039
|View full text |Cite
|
Sign up to set email alerts
|

Cholera Toxin Production Induced upon Anaerobic Respiration is Suppressed by Glucose Fermentation in Vibrio cholerae

Abstract: The causative agent of pandemic cholera, Vibrio cholerae, infects the anaerobic environment of the human intestine. Production of cholera toxin (CT), a major virulence factor of V. cholerae, is highly induced during anaerobic respiration with trimethylamine N-oxide (TMAO) as an alternative electron acceptor. However, the molecular mechanism of TMAO-stimulated CT production is not fully understood. Herein, we reveal that CT production during anaerobic TMAO respiration is affected by glucose fermentation. When t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…For example, tetrathionate respiration provides Salmonella enterica serovar Typhimurium with advantage to colonize the inflamed intestines [27,28]. Cholera toxin production by Vibrio cholerae is also enhanced by anaerobic respiration [29,30]. Recently, it was demonstrated that the ability of L. monocytogenes to perform extracellular electron transfer conferred a clear fitness advantage in vivo [31].…”
Section: Discussionmentioning
confidence: 99%
“…For example, tetrathionate respiration provides Salmonella enterica serovar Typhimurium with advantage to colonize the inflamed intestines [27,28]. Cholera toxin production by Vibrio cholerae is also enhanced by anaerobic respiration [29,30]. Recently, it was demonstrated that the ability of L. monocytogenes to perform extracellular electron transfer conferred a clear fitness advantage in vivo [31].…”
Section: Discussionmentioning
confidence: 99%
“…Stringent response stimulated by the accumulation of guanosine pentaphosphate/tetraphosphate (p)ppGpp under stress conditions play an important role in the growth and virulence of V. cholerae . Administration of glucose, which is present in the oral rehydartion solution might reduce (p)ppGpp-mediated CT-production and growth of the pathogen under the influence of anaerobic glucose metabolism (Oh et al, 2016 ). Genome-wide screening has revealed that flagellin FlaC is involved in flagellum function and toxin production at higher (p)ppGpp levels (Kim et al, 2018 ).…”
Section: Flagellar Regulatory Systemmentioning
confidence: 99%
“…In addition to TorSR, TMAO respiration in V. cholerae is also governed by the catabolite repression protein (CRP), impairing TMAO reduction when glucose is available under anaerobic conditions. It has been proposed that the depletion of intracellular cAMP under high glucose concentrations leads to the inactivation of CRP and, as a consequence, expression of the TMAO reductase TorA is abrogated (Oh et al, 2015).…”
Section: Anaerobic Tmao Respirationmentioning
confidence: 99%